Social Statistics - Moore, Mel (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The focus of this course is the application of basic statistical techniques to sociological questions. The goals of this course include developing an appreciation for the role of statistics in social research and everyday life, understanding the conceptual basis for statistics, and the development of your ability to organize and present data using fundamental statistics.